2012
DOI: 10.1186/1472-6882-12-233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electroacupuncture in postanesthetic shivering during regional anesthesia: a randomized controlled trial

Abstract: BackgroundShivering during regional anesthesia is a common complication and is related to a decrease in the patient’s core body temperature. Previous studies have shown that acupuncture on specific acupoints can preserve core body temperature. The present study evaluated the effect of electroacupuncture in preventing the shivering caused by regional anesthesia.MethodsThis prospective and randomized controlled study analyzed the data from 80 patients undergoing urological surgery, who were classified as ASA I o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 31 publications
0
20
1
1
Order By: Relevance
“…Stener-Victorin et al [24] proposed that the low frequency (below 10 Hz) EA, at acupoints of lower extremities, attenuates sympathetic nerve activity, which may mediate muscle shivering. EA also leads to peripheral vasoconstriction and interrupts the core-to-peripheral redistribution of heat that results from spinal anesthesia [12]. Furthermore, several experimental studies describe the effects of acupuncture for the prevention and treatment of shivering.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Stener-Victorin et al [24] proposed that the low frequency (below 10 Hz) EA, at acupoints of lower extremities, attenuates sympathetic nerve activity, which may mediate muscle shivering. EA also leads to peripheral vasoconstriction and interrupts the core-to-peripheral redistribution of heat that results from spinal anesthesia [12]. Furthermore, several experimental studies describe the effects of acupuncture for the prevention and treatment of shivering.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several experimental studies describe the effects of acupuncture for the prevention and treatment of shivering. Yeh et al [12] stated that when EA is performed at low frequency (3 Hz) on ST 36 and ST 37, the core temperature is elevated and the redistribution of heat is inhibited, resulting in a reduced incidence of postanesthetic shivering. Lin et al [13] reported that when ST 36 was stimulated, oral temperature was increased, while cutaneous temperature of the limbs was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These involved therapeutic modalities including acupuncture injection, 38,39 electroacupuncture, 40,41 transcutaneous electro acupoint stimulation, 42,43 auricular acupuncture, 44,45 Korean hand acupressure, 46,47 and capsicum plaster used on acupuncture points. 48,49 These studies were excluded as they did not meet the selection criteria.…”
Section: Selection Of Papersmentioning
confidence: 99%